A method to calculate the conversion efficiency of a rectenna. Issue 9 (31st August 2018) - Wan, Shaopeng; Huang, Kama; Liu, Yilin
Abstract: This article studies the working principle of a rectenna which is a combination of an antenna and a rectifying circuit. In the simulation, the working properties of the rectifying circuit can be represented by two characteristic curves which are extracted from it, and these two curves are independent of the device which is connected with it. The measured results demonstrate that the data calculated by the two curves can be used to accurately describe the conversion efficiency of the rectifying circuit. Furthermore, the two curves are used to represent the rectifying circuit in the calculation of the rectenna conversion efficiency. In addition, with the characteristic impedance of the antenna, the calculation equation is given. In the experiment of the rectenna, the measured conversion efficiency of the rectenna is in agreement with the data calculated by the proposed equation, which proves the accuracy of this method.